(untitled) (Journal of Hama University, 2024)
Aim: This research aims to evaluate different techniques for caries (conventional stainless steel Burs- Smart Burs II - Chemomechanical Technique - dental laser) in the process of removing dental caries, by investigating the effectiveness (time required to completely caries removal process) and efficiency (detecting the presence of bacterial accumulations) after the completion of the process of dental caries removal. Material and Methods: The study included a caries removal of (60) human molars with occlusal caries. The sample was divided randomly into four equal groups :the caries of each group was removed only by one of caries removal techniques. The time required to remove dentinal caries for each sample was calculated from the beginning to completion. The samples were then subjected to histological study in order to detect the presence of remaining bacterial accumulations after the completion of removal dental caries. Results: The caries removal technique using a dental laser was the most time-consuming in order to complete the complete removal of dental caries, with statistically significant differences compared to the rest of the caries removal techniques. The levels of bacterial accumulation after the end of caries removal was the lowest in the laser caries removal group, While the highest levels of bacterial accumulation were associated with Smart Burs II group. There were no differences in the levels of residual bacterial accumulation after caries removal using the conventional technique and the chemical-mechanical technique Conclusions: This laboratory experiment demonstrated the efficiency of the dental laser and the effectiveness of the chemo-mechanical technique as well as the conventional technique in the context of the process of removing dental caries.